Closing the Loop on E‐waste: A Multidisciplinary Perspective. (26th August 2017) - Bridgens, Ben; Hobson, Kersty; Lilley, Debra; Lee, Jacquetta; Scott, Janet L.; Wilson, Garrath T.
Summary: This paper describes the challenges faced, and opportunities identified, by a multidisciplinary team of researchers developing a novel closed loop system to recover valuable metals and reduce e‐waste, focusing on mobile phones as a case study. This multidisciplinary approach is contrasted with current top‐down approaches to making the transition to the circular economy (CE). The aim of the research presented here is to develop a product service system (PSS) that facilitates the recovery of valuable functional components and metals from mobile phone circuit boards. To create a holistic solution and limit unintended consequences, in addition to technological solutions, this paper considers appropriate component lifetimes; the (often ignored) role of the citizen in the circular economy; customer interaction with the PSS; environmental life cycle assessment; and social impacts of the proposed PSS. Development of enabling technologies and materials to facilitate recovery of components and metals and to provide an emotionally durable external enclosure is described. This research also highlights the importance of understanding value in the CE from a multifaceted and interdisciplinary perspective.